1994
DOI: 10.1159/000113566
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem Reticular Nuclei that Project to the Thalamus in Rats: A Retrograde Tracer Study; pp. 1–22

Abstract: The precise nuclear origins of projections from the brainstem reticular formation to the thalamus were identified in rats using two retrograde tracing substances: wheat germ agglutinin-horseradish peroxidase conjugate, and Fluoro-Gold. Injections of these tracers were made into a variety of thalamic nuclei, including the intralaminar nuclei (most of these also involved the lateral part of the mediodorsal nucleus), the central part of the mediodorsal nucleus, the ventrolateral/ ventromedial nuclei, and the vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…However, double-labeled neurons were very few. Outside the PPN/LDT complex, reticular projections to the ventrobasal complex were modest, as indicated also in previous studies (Vertes et al 1986;Vertes and Martin 1988;Newman and Ginsberg 1994;and their references). A relatively strong, bilateral thalamopetal projection arises in the deep mesencephalic reticular nucleus, but occasional double-labeled neurons were seen only in the largest injections, such as in case R1663.…”
Section: Brainstemsupporting
confidence: 82%
“…However, double-labeled neurons were very few. Outside the PPN/LDT complex, reticular projections to the ventrobasal complex were modest, as indicated also in previous studies (Vertes et al 1986;Vertes and Martin 1988;Newman and Ginsberg 1994;and their references). A relatively strong, bilateral thalamopetal projection arises in the deep mesencephalic reticular nucleus, but occasional double-labeled neurons were seen only in the largest injections, such as in case R1663.…”
Section: Brainstemsupporting
confidence: 82%
“…The linear nucleus (Fig. 26A,B) was included in the lateral reticular nucleus on the basis of cytological, enzyme histochemical, and anterograde and retrograde axonal tracing studies (Newman and Ginsberg, 1994;Ruigrok, 2004;Fu et al, 2009). The main ventrocaudal portion of the lateral reticular nucleus is located within the ascending spinal fibers of the anterolateral funiculus.…”
Section: Lateral Reticular Nucleusmentioning
confidence: 99%
“…Direct projections to the PPN from the vestibular nuclei (Woolf and Butcher, 1989, Hazrati and Parent, 1992, Horowitz et al, 2005), deep cerebellar nuclei (Hazrati and Parent, 1992, Teune et al, 2000), premotor and motor cortices (Matsumura et al, 2000, Aravamuthan et al, 2007), and frontal eye fields (Stanton et al, 1988b, Matsumura et al, 2000) have been shown in primates or rodents. The PPN also projects to multiple thalamic nuclei including the ventral posterior thalamus (Smith et al, 1988, Steriade et al, 1988, Lavoie and Parent, 1994b, Newman and Ginsberg, 1994, Erro et al, 1999) and is reciprocally connected with multiple basal ganglia nuclei (Parent and Smith, 1987, Lavoie and Parent, 1994b, a, Charara et al, 1996). Descending projections include primarily non-cholinergic efferents to the cervical and thoracic spinal cord (Goldsmith and van der Kooy, 1988, Rye et al, 1988, Spann and Grofova, 1989, Skinner et al, 1990a, Aravamuthan et al, 2007) and primarily cholinergic efferents to the pontine and medullary reticular formations (Garcia-Rill and Skinner, 1987, Skinner et al, 1990b, Takakusaki et al, 1996, Whelan, 1996, Jordan, 1998, Garcia-Rill et al, 2001) including projections to a large portion of medullary reticulospinal neurons (Garcia-Rill and Skinner, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Like the PPN, the central mesencephalic reticular formation (cMRF, variably known as the deep mesencephalic nucleus and the midbrain reticular formation) receives inhibitory input from the substantia nigra pars reticulata and internal segment of the globus pallidus (Veazey and Severin, 1982, Hay-Schmidt and Mikkelsen, 1992, Rodriguez et al, 2001), sends GABAergic projections to the ventral thalamus (Bowsher, 1975, Veazey and Severin, 1980a, Newman and Ginsberg, 1994, Rodriguez et al, 2001), and sends descending projections to the cervical spinal cord (Veazey and Severin, 1980b, Warren et al, 2008). In addition, the cMRF directly projects to the PPN (Rodriguez et al, 2001).…”
Section: Introductionmentioning
confidence: 99%